Design and implementation of signaling and traffic control for AAPN - Deng, Yong (University of Ottawa (Canada), 2007)
Although all-photonic network is a hot topic in recent years, most networks still do not have the ability to achieve high utilization and to allocate bandwidth dynamically and efficiently to an edge node. Many theoretical works and publications have been done in this field. However, up to now there is no commercial or lab product in this area. AAPN (Agile All-Photonic Network) is one research project focusing on these issues while at the same time avoid blocking and starvation. We designed and implemented the whole AAPN signaling protocols under Linux and produced a lab prototype under the AAPN framework. To the best of our knowledge, this is the first AAPN prototype in the world. While bandwidth has increased so much after the Internet first came to reality, user's request increases even much faster. Congestion can not be avoided if there is no algorithm to control it. The XCP (eXplicit Control Protocol) algorithm is a promising congestion control method that uses explicit feedback. However, XCP does not work when the link capacity changes with time. In this research we designed a modified version, the XCP-CL (XCP of Cross-Layer design) algorithm, that works successfully on the AAPN network. Extensive simulation results have verified that XCP-CL has a much better performance compared to the original XCP algorithm.
Keywords: Engineering, Electronics and Electrical.